Location and logistics - Sibel A. Alumura; Bahar Y. Karab; M. Teresa Melo (Hochschule für Technik und Wirtschaft des Saarlandes, Fakultät für Wirtschaftswissenschaften, 2013)
Facility location decisions play a critical role in designing logistics networks. This article provides some guidelines on how location decisions and logistics functions can be integrated into a single mathematical model to optimize the configuration of a logistics network. This will be illustrated by two generic models, one supporting the design of a forward logistics network and the other addressing the specific requirements of a reverse logistics network. Several special cases and extensions of the two models are discussed and their relation with the scientific literature is described. In addition, some interesting applications are outlined that demonstrate the interaction of location and logistics decisions. Finally, new research directions and emerging trends in logistics network design are provided.
Keywords: 650; forward logistics network design; reverse logistics network design; models; applications